Emerging types of Shiga toxin-producing E. coli (STEC) O178 present in cattle, deer, and humans from Argentina and Germany - Miko, Angelika; Rivas, Marta; Bentancor, Adriana; Delannoy, Sabine; Fach, Patrick; Beutin, Lothar (Frontiers in Cellular and Infection Microbiology, 2014)
More than 400 serotypes of Shiga toxin-producing Escherichia coli (STEC) have been implicated in outbreaks and sporadic human diseases. In recent years STEC strains belonging to serogroup O178 have been commonly isolated from cattle and food of bovine origin in South America and Europe. In order to explore the significance of these STEC strains as potential human pathogens, 74 German and Argentinean E. coli O178 strains from animals, food and humans were characterized phenotypically and investigated for their serotypes, stx-genotypes and 43 virulence-associated markers by a real-time PCR-microarray. The majority (n = 66) of the O178 strains belonged to serotype O178:H19. The remaining strains divided into O178:H7 (n = 6), O178:H10 (n = 1), and O178:H16 (n = 1). STEC O178:H19 strains were mainly isolated from cattle and food of bovine origin, but one strain was from a patient with hemolytic uremic syndrome (HUS). Genotyping of the STEC O178:H19 strains by pulsed-field gel electrophoresis revealed two major clusters of genetically highly related strains which differ in their stx-genotypes and non-Stx putative virulence traits, including adhesins, toxins, and serine-proteases. Cluster A-strains including the HUS-strain (n = 35) carried genes associated with severe disease in humans (stx2a, stx2d, ehxA, saa, subAB1, lpfAO113, terE combined with stx1a, espP, iha). Cluster B-strains (n = 26) showed a limited repertoire of virulence genes (stx2c, pagC, lpfAO113, espP, iha). Among O178:H7 strains isolated from deer meat and patients with uncomplicated disease a new STEC variant was detected that is associated with the genotype stx1c/stx2b/ehxA/subAB2/espI/[terE]/espP/iha. None of the STEC O178 strains was positive for locus of enterocyte effacement (LEE)- and nle-genes. Results indicate that STEC O178:H19 strains belong to the growing group of LEE-negative STEC that should be considered with respect to their potential to cause diseases in humans.